Telenursing Applications in Treatment Compliance among Patients with Mental Disorders - Noorwahyu Trihidayat; Mamnuah Mamnuah; Yuli Isnaeni (Journal of Health Technology Assessment in Midwifery, 2023)
Background: Treatment adherence is one of the problems in the treatment of patients with mental disorders. Telenursing is a part of telemedicine that plays an important role in providing modern nursing care, improving the quality of care, and accessing services quickly. Purpose: To describe the use of telenursing in medication adherence in patients with mental disorders. Methods: Literature review searches were conducted on PubMed, Wiley, and Google scholar. The search strategy used the keywords "telenursing" OR "telehealth" AND Medication Adherence" AND "Mental disorder". The inclusion criteria are the article uses a Randomized Control Trial design, the article does not limit the place or location, published in the last 5 years (2017-2021), in English and free full text. While the exclusion criteria are qualitative research, mixed-method, journal review/systematic review, published under 2017, the title and abstract do not match. Results: Four articles matched the inclusion criteria and topics. From four articles, it was found that the application of telenursing in mental disorders uses TIPS (Telephone Intervention Problem Solving), LEAN (Lay health supporters, E-platform, Award, and iNtegration), cellular applications such as WhatsApp, WeChat, Telegram, Line. Conclusion: With a smartphone application, it can provide a signal, reminder, or education, in overcoming forgetting or not wanting to take medicine or forgetting to control schedules and can be adjusted to resource and geographical conditions. The use of telenursing can help people with mental disorders to increase their belief in the importance of treatment, increase treatment adherence, reduce the length of hospital stay.